The Effect of the Implementation of Human Resource Score Card on Performance at Permata Depok Hospital - Hawariyah Hawariyah; Acim Heri Iswanto; Alfatih S. Manggabarani; Yudi Nur Supriadi (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
Performance is assessed to see the extent to which the actions taken by a person in carrying out certain jobs/activities within an organization or company by carrying out the principles of the right mechanism or method in comparing what is done with the results achieved. The purpose of this study was to prove the effectiveness of the human resource score card (competence, job description and measurement) on performance at Permata Depok Hospital. The research method used is descriptive quantitative. The research sample was 100 employees of Permata Depok Hospital. The research instrument in the form of a questionnaire and data analysis using Structural Equation Modeling with Partial Least Square (PLS). The results of the study found that competence had a positive effect on employee performance at Permata Depok Hospital with tcount 3.904 > ttable 1.986. job description has a positive effect on employee performance at Permata Depok Hospital with tcount 4,620 > t table 1,986. The measurement has a positive effect on employee performance at Permata Depok Hospital with tcount 4,620 > ttable 1,986. Competence and Job description, Measurement have a positive effect on employee performance at Permata Depok Hospital with tcount 2,540 > ttable 1,986. The conclusion of the study is that there is an effect of human resource score card (competence, job description and measurement) on performance at Permata Depok Hospital. Research suggestions need to accelerate the procurement of Hospital Information Systems (SIRS). Information integration is a key element in hospital management. Integrated information allows planning, control and supervision to be carried out properly, quickly, precisely and directed. Keywords : job description, measurement, performance, HR scorecard